Over a million students use our free study notes to help them with their homework
Let's think backwards - what can we multiply to get this result?First, let's take a simpler example, an expression:(x-1)(x-2). We multiply 1st term of the 1st brackets by terms of the 2nd bracket and then...
Mary = 20km/h Jason = 15km/h s = d/t After 1.5 hours, Mary = 30km and Jason = 22.5km 30 + 22.5 = 52.5km
Factorising gives: y = (x+2)(x+1) = 0. y only equals 0 when (x+2)=0 or (x+1)=0. Therefore x=-2 or x=-1
Equation 1: 3x+y= 11, Equation 2: 2x+y=8. You want to find out what x is and what y is.In both equations there is only 1 unit of y therefore it is easiest to rearrange the first equation so that it equals...
18/(3+2)=3.63x3.6=10.8 2x3.6=7.210.8x2.8=30.247.2x3.5=25.230.24+25.2=55.44
←
410
411
412
413
414
→
Internet Safety
Payment Security
Cyber
Essentials